A case of Avar period trepanation from Croatia - Premužić, Zrinka; Šikanjić, Petra Rajić; Rapan Papeša, Anita (Anthropological Review, 2016)
The Avar period cemetery of Nuštar, situated in continental Croatia, is dated to the 8th and the beginning of the 9th century. Rescue archaeological excavation yielded 196 burials. During analysis of human skeletal remains, an individual with a large cranial lesion caused by trepanation was found. Trepanation is a surgical procedure performed on the skull in order to remove a fragment of the bone using a sharp instrument or drill. It has been practiced in various regions since the prehistoric period for both medical and ritual reasons. The aim of this paper is to provide a description of the observed lesion based on macroscopic appearance accompanied by radiography, computed tomography scanning and 3D optical scanning. Furthermore, possible cause and employed technique are taken into consideration, as well as cultural and historical implications of the case.